Dynamics of Endocytosis and Degradation of Antibody-Drug Conjugate T-DM1 in HER2 Positive Cancer Cells - Liang K; Mei S; Gao X; Peng S; Zhan J (Dove Medical Press, 2021)
Keying Liang, Shengsheng Mei, Xiangzheng Gao, Shanshan Peng, Jinbiao Zhan Department of Biochemistry, Cancer Institute of the Second Affiliated Hospital (Key Laboratory of Cancer Prevention and Intervention, China National Ministry of Education), School of Medicine, Zhejiang University, Hangzhou, 310058, People's Republic of ChinaCorrespondence: Jinbiao ZhanDepartment of Biochemistry, Cancer Institute of the Second Affiliated Hospital (Key Laboratory of Cancer Prevention and Intervention, China National Ministry of Education), School of Medicine, Zhejiang University, Hangzhou, Zhejiang, 310058, People's Republic of ChinaTel/Fax +86 571-88208273Email jzhan2k@zju.edu.cnPurpose: T-DM1 is an antibody-drug conjugate (ADC) consisting of trastuzumab and DM1 linked together. T-DM1 binds to human epidermal growth factor receptor-2 (HER2) in tumors and then triggers the endocytosis of T-DM1 and release of payload. Therefore, endocytosis efficacy is considered as a critical step for the initiation of T-DM1 therapy; however, the endocytosis mechanism of T-DM1 remains poorly understood. Meanwhile, HER2 is regarded as an internalization-resistant receptor, which hinders the endocytosis and effectiveness of T-DM1. The present study is to explore the T-DM1 endocytosis pathway, which may provide insights into the internalization mechanism of ADCs and help to improve efficacy.Methods: Confocal microscopy and flow cytometry were used to analyse T-DM1 intracellular trafficking and endocytosis efficiency, while Western blot assay was performed to detect T-DM1 degradation.Results: We found that intracellular T-DM1 was increased to 50% within 12 h. T-DM1 was colocalized with cholera toxin B (CTxB), a lipid raft marker, within 2 h and then degraded in lysosome. Upon overexpression of caveolin-1 (CAV-1) and utilization of caveolae/lipid-raft disruptors, we found that temporal CAV-1 upregulation significantly facilitated T-DM1 endocytosis and degradation, whereas nystatin and lovastatin disrupted caveolae/lipid-raft structure and inhibited T-DM1 degradation. We demonstrate that T-DM1 internalizes through the lipid raft-mediated endocytosis in a CAV-1 dependent manner, rather than through the clathrin-mediated endocytosis in HER2-positive cancer cells.Conclusion: Our findings suggest that modulation of the caveolae/lipid-raft mediated endocytosis may be a possible option for improving the clinical therapeutic effect of T-DM1 because it plays a key role in regulating T-DM1 internalization.Keywords: antibody-drug conjugate, T-DM1, endocytosis, lipid rafts, caveolae, caveolin-1